Studi Kualitatif Tentang Analisis Strategi Komunikasi Pemasaran Pada Peluncuran Produk Cloud Raya Di Pt Wowrack Indonesia - Femmilia, Nita (Humantech : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
The rapid development of digitalization means cloud computing technology is playing an increasingly important role as a business driver. This is indicated by the number of companies turning to digitizing their businesses and expanding the cloud to various business sectors ranging from manufacturing, finance, and services. The need for a business for cloud computing products has made many cloud computing companies appear in Indonesia. The presence of cloud computing companies today creates increasingly fierce competition in the computing business. In capturing the market, these computing business actors use various strategies to increase their company's market share. This study reviews the analysis of marketing communication strategies at the launch of the Raya cloud product at PT Wowrack Indonesia. PT Wowrack Indonesia is an information technology company that continues to compete in the midst of rampant business digitalization, so in 2020 Wowrack launched a new service product, Cloud Raya, using a marketing communication strategy through the Integrated Marketing Communication (IMC) program. This study uses a mixed-method approach based on the conceptual framework of integrated marketing communication, marketing communication mix, and traditional response hierarchies. The results of the study indicate that the application of integrated marketing communication to new products is expected to get a positive response and good effectiveness in attention, interest, desire, and action towards a new service product.